Pengaruh Budaya Organisasi dan Kompensasi Terhadap Kinerja Pegawai Staff Administrasi Universitas Sarjanawiyata Tamansiswa - andreas setya prabawa (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study was to describe (1) the influence of organizational culture on the performance of administrative staff employees of the University of Sarjanawiyata Tamansiswa Yogyakarta, (2) to determine the effect of compensation on the performance of Administrative Staff staff at Sarjanawiyata Tamansiswa Yogyakarta, (3) to determine together with the performance of UST Yogyakarta Administrative Staff. The type of data of this study uses the independent variable namely Organizational Culture and Compensation, and the variable value is the kinship. The population in this research is 160 UST Administrative Staff Staff in Yogyakarta. The results of this study are that organizational culture variables influence the performance of UST Yogyakarta administrative staff employees, while the compensation variable does not affect the performance of administrative staff at UST Yogyakarta. From the value of the coefficient of determination (R Square) of 0.228 which is the result of squaring of the correlation coefficient or R. The magnitude of the coefficient of determination (R-Square) is 0.228 or equal to 22.8% which implies that organizational culture (X1) and compensation (X2) simultaneously the simultaneous effect on performance (Y) is 22.8% while the rest (100% -22.8% = 77.2%) is influenced by other variables outside of this regression. Keywords: Organizational culture, compensation, performance.